KINERJA PELAYANAN JALUR PEDESTRIAN DI PASAR ACEH MENGGUNAKAN METODE CUSTOMER SERVICE INDEX (CSI) - Cut Mutiawati; Fitrika Mita Suryani; Muhammad Isya; Ruhdi Faisal (Prodi Magister Teknik Sipil Unsyiah, 2021)
The pedestrians’ sidewalk is part of the transportation infrastructure in the city that has a role and function in providing service and convenience to the citizen. One of the cities that actively build pedestrian sidewalks is Banda Aceh. There were some problems in the sidewalk; the up and down sidewalk, slippery surface, high ramp, and many other obstacles. Thus, this research aimed to measure the pedestrians' satisfaction in three streets in Pasar Aceh, namely Chik Pante Kulu street, K.H. Dahlan street, and Diponegoro street, by using the Customer Satisfaction Index (CSI). The analysis result indicated that most pedestrians’ sidewalk facilities need to prioritize their performance improvement. It was concluded from the sidewalk performance in the three streets evaluation. The dominant average value is